Analisis Pencahayaan Ruangan Pada Ruang Kelas Di Universitas Singaperbangsa Karawang Menggunakan Dialux Evo 9.1 - Gita Yusvita (Fakultas Teknik, 2021)
Room lighting is an important factor in the work environment to improve performance and is also a factor in occupational health and safety. Lighting that is not up to standard can cause eye fatigue, resulting in decreased worker performance. In educational institutions, the classroom is the room that is used most often compared to other rooms, so that the classroom needs adequate lighting to support the occurrence of teaching and learning activities in the room. In two classrooms at University of Singapperbangsa Karawang, indoor lighting analysis was carried out to determine the level of lighting. The purpose of this study is to determine whether the lighting level in the classroom is in accordance with the SNI 03-6575-2001 standard, which is 250 Lux. Based on the calculation of the number of lights, in class 1 it takes 8 lights and in class 2 it takes 14 lights. Calculations using Dialux Evo 9.1 in class 1 the lighting level during the day are 280 lux and at night is 187 Lux, while in class 2 the lighting level is 189 Lux during the day and 199 Lux at night. This shows that it is necessary to repair the lighting installation.